2015
DOI: 10.1523/jneurosci.3160-14.2015
|View full text |Cite
|
Sign up to set email alerts
|

Neural Correlates of Object-Associated Choice Behavior in the Perirhinal Cortex of Rats

Abstract: The perirhinal cortex (PRC) is reportedly important for object recognition memory, with supporting physiological evidence obtained largely from primate studies. Whether neurons in the rodent PRC also exhibit similar physiological correlates of object recognition, however, remains to be determined. We recorded single units from the PRC in a PRC-dependent, object-cued spatial choice task in which, when cued by an object image, the rat chose the associated spatial target from two identical discs appearing on a to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
42
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(59 citation statements)
references
References 62 publications
8
42
0
Order By: Relevance
“…Both studies provided evidence of spatial "memory" fields at prior locations when objects were moved in or removed from the environment, whereas Deshmukh et al (2011) also provided examples of activity similar to place field firing when objects were presented. In addition, studies on earlier stages of information processing before LEC and MEC (i.e., in the PRC and postrhinal cortex) have also reported mixed selectivity of neuronal activity in animals performing memory tasks where objects and spatial choices are relevant (Furtak et al, 2012;Ahn and Lee, 2015). The present findings suggest that both LEC and MEC also represent organizations of objects and events within spatial contexts (see also and that even PRC exhibits a combination of object and spatial coding.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Both studies provided evidence of spatial "memory" fields at prior locations when objects were moved in or removed from the environment, whereas Deshmukh et al (2011) also provided examples of activity similar to place field firing when objects were presented. In addition, studies on earlier stages of information processing before LEC and MEC (i.e., in the PRC and postrhinal cortex) have also reported mixed selectivity of neuronal activity in animals performing memory tasks where objects and spatial choices are relevant (Furtak et al, 2012;Ahn and Lee, 2015). The present findings suggest that both LEC and MEC also represent organizations of objects and events within spatial contexts (see also and that even PRC exhibits a combination of object and spatial coding.…”
Section: Discussionmentioning
confidence: 99%
“…By contrast, LEC neurons exhibit little spatial specificity in this behavioral situation (Hargreaves et al, 2005) and PRC neurons exhibit none (Deshmukh et al, 2012). Conversely, in experiments where animals perform object recognition or discrimination tasks, PRC and LEC neurons fire during the presentation of specific odor (in rats) or visual (in monkeys) cues, during maintenance of nonspatial memories, or associated with behavioral responses, but firing patterns associated with the animals' location in space were not examined (Suzuki et al, 1997;Young et al, 1997;Yanike et al, 2009;Igarashi et al, 2014;Ahn and Lee, 2015;Brown and Banks, 2015). Some recent studies have identified activity in PRC and LEC neurons associated with objects or visual patterns in particular places as animals explore an open field (Deshmukh and Knierim, 2011;Deshmukh et al, 2012;Tsao et al, 2013) or traverse a circular path in a maze (Burke et al, 2012;Neunuebel et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…In the three areas, representations of identical events are most closely associated (correlation of odd/even trials). Thus, although PRC, LEC and MEC exhibit similarity in mixed selectivity at the single neuron level, RSA reveals that information is organized in distinct but complementary ways (see also Ahn and Lee, 2015; Beer et al, 2013; Deshmukh and Knierim, 2011; Ohyama et al, 2012). …”
Section: The Hippocampus Mec Lec Ofc and Perirhinal Cortex Create mentioning
confidence: 99%
“…While age‐related dysfunction within hippocampal circuits is well‐documented (Burke & Barnes, ; Burke & Barnes, ; Rosenzweig & Barnes, ; Wilson, Gallagher, Eichenbaum, & Tanila, ), the emergence of disrupted function across cortical subregions of the medial temporal lobe has not been fully examined. Thus, despite the established importance of perirhinal cortex in forming high‐order sensory representations and discriminating between them (Ahn & Lee, ; Bartko, Winters, Cowell, Saksida, & Bussey, ,b; Byun & Lee, ; Graham, Barense, & Lee, ), the contribution of change in neural communication across these circuits to age‐related discrimination deficits remains unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Both animal and human studies have reported declines in stimulus discrimination abilities with age, yet distinct potential mechanisms have been highlighted between different species. The ability to discriminate between similar objects has been shown to require the perirhinal cortex in rats (Ahn & Lee, ; Bartko et al, ; Eacott, Machin, & Gaffan, ; Winters, Bartko, Saksida, & Bussey, ; Hales, Broadbent, Velu, Squire, & Clark, ) and monkeys (Baxter & Murray, ; Buckley & Gaffan, ; Bussey, Saksida, & Murray, ). On the other hand, the majority of neuroimaging studies that have directly investigated object discrimination abilities in humans have shown a consistent relationship between task performance and activation within the CA3/dentate gyrus circuit (Bakker, Albert, Krauss, Speck, & Gallagher, ; Bakker, Kirwan, Miller, & Stark, ; Bakker et al, ; Doxey & Kirwan, ; Kirwan & Stark, ; Lacy, Yassa, Stark, Muftuler, & Stark, ; Motley & Kirwan, ; Reagh & Yassa, ; Yassa et al, , Yassa, Mattfeld, Stark, & Stark, ).…”
Section: Introductionmentioning
confidence: 99%